2012
DOI: 10.1097/ccm.0b013e318232e2fc
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a lean rounding process in a pediatric intensive care unit*

Abstract: Implementation of a lean-focused, patient-centric rounding structure stressing essential processes was associated with increased timeliness and efficiency of rounds, improved staff and customer satisfaction, improved throughput, and reduced attending physician man-hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 5 publications
1
48
1
5
Order By: Relevance
“…One study found that a lean, focused, patient-centric rounding structure not only increased patient and staff satisfaction but also improved patient throughput and decreased attending physicians' hours used. 11 Lean and six-sigma methods 12 have also been used to streamline rounding by standardizing practices and eliminating nonessential activities such as ''pre-rounding.'' 13,14 Habit 3: Put First Things First Time management was cited by Sandhu et al 1 as an important educational component of family-centered bedside rounds.…”
Section: Habit 1: Be Proactivementioning
confidence: 99%
“…One study found that a lean, focused, patient-centric rounding structure not only increased patient and staff satisfaction but also improved patient throughput and decreased attending physicians' hours used. 11 Lean and six-sigma methods 12 have also been used to streamline rounding by standardizing practices and eliminating nonessential activities such as ''pre-rounding.'' 13,14 Habit 3: Put First Things First Time management was cited by Sandhu et al 1 as an important educational component of family-centered bedside rounds.…”
Section: Habit 1: Be Proactivementioning
confidence: 99%
“…Vats et al 25 afirmam que o mapeamento dos processos oferece oportunidades para as organizações de saúde e suas iniciativas de melhoria contínua. A eficácia dos processos pode ser alcançada a partir de indicadores e de treinamentos para os trabalhadores, fazendo com que os processos sejam desenvolvidos com base na sua real necessidade 20 .…”
unclassified
“…Os trabalhadores de saúde devem estar cientes que a utilidade dessas iniciativas pode melhorar os resultados almejados e/ou reduzir os custos dos cuidados em saúde (VATS et al, 2012), tornando-se, então, uma tendência mundial no quesito qualidade hospitalar.…”
Section: Através Do Trabalho Inicial Do Professor Ernest Amony Codmanunclassified
“…A metodologia lean empregada em hospitais, com foco nos processos essenciais e análise de cenários, tem como objetivo melhorar e padronizar processos centrados no paciente, agregando valor aos serviços oferecidos, aumentando a eficiência dos processos e a satisfação dos clientes, com a diminuição dos recursos desnecessários (MACFARLANE, 2014;BRACKETT, COMER e WHICHELLO, 2013;SEIDL e NEWHOUSE, 2012;VATS et al, 2012;VATS, GOIN e FORTENBERRY, 2011;GROVE et al, 2010;MAZZOCATO et al, 2010;YOUNG e MCCLEAN, 2008 A acreditação hospitalar visa propor um roteiro que oriente a gestão hospitalar aos requisitos mínimos para processos e resultados, criando uma escala de maturidade que avalia o grau em que práticas e procedimentos de trabalho são realizados e incorporados à rotina de atividades dos hospitais, apontando para dois objetivos principais: paciente e gestão (ALÁSTICO e TOLEDO, 2013;YOUSEFIAN et al, 2013;BRAITHWAITE et al, 2012;RUNNELS e CARRERA, 2012;AMERIOUN et al, 2011;FORTES, MATTOS e BAPTISTA, 2011;SHAW et al, 2010a;SHAW et al, 2010b).…”
Section: Destacam-se As Normas Da International Organization For Stanunclassified
See 1 more Smart Citation